Optimization of a fluorescent-mRNA based real-time assay for precise kinetic measurements of ribosomal translocation. Issue 12 (2nd December 2021) - Kim, Changil; Holm, Mikael; Mandava, Chandra Sekhar; Sanyal, Suparna
ABSTRACT: Kinetic characterization of ribosomal translocation is important for understanding the mechanism of elongation in protein synthesis. Here we have optimized a popular fluorescent-mRNA based translocation assay conducted in stopped-flow, by calibrating it with the functional tripeptide formation assay in quench-flow. We found that a fluorescently labelled mRNA, ten bases long from position +1 (mRNA+10), is best suited for both assays as it forms tripeptide at a fast rate equivalent to the longer mRNAs, and yet produces a large fluorescence change upon mRNA movement. Next, we compared the commonly used peptidyl tRNA analog, N-acetyl-Phe-tRNA Phe, with the natural dipeptidyl fMet-Phe-tRNA Phe in the stopped-flow assay. This analog translocates about two times slower than the natural dipeptidyl tRNA and produces biphasic kinetics. The rates reduce further at lower temperatures and with higher Mg 2+ concentration, but improve with higher elongation factor G (EF-G) concentration, which increase both rate and amplitude of the fast phase significantly. In summary, we present here an improved real time assay for monitoring mRNA-translocation with the natural- and an N-Ac-analog of dipeptidyl tRNA. GRAPHICAL ABSTRACT: uf0001